“Shalom, Shalom, Shalom Israel!” Jews and Judaism in Helmut Gollwitzer’s Life and Theology - McMaken, W. Travis (Studies in Christian-Jewish Relations, 2015)
This essay examines the place of Israel in the life and thought of Helmut Gollwitzer, an important German theologian of the mid-twentieth century. It examines his experiences with the Confessing Church struggle against the Nazi Reich, his solidarity with the Jewish people in the wake of the November 1938 pogrom, and his leadership in Jewish-Christian dialogue after the conclusion of the second world war. The essay ends with suggestions from Gollwitzer's example for Christians who engage in Jewish-Christian dialogue today.